2023
DOI: 10.3389/fmicb.2022.987164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical modifications of tannins on their antimicrobial and antibiofilm effect against Gram-negative and Gram-positive bacteria

Abstract: BackgroundTannins have demonstrated antibacterial and antibiofilm activity, but there are still unknown aspects on how the chemical properties of tannins affect their biological properties. We are interested in understanding how to modulate the antibiofilm activity of tannins and in delineating the relationship between chemical determinants and antibiofilm activity.Materials and methodsThe effect of five different naturally acquired tannins and their chemical derivatives on biofilm formation and planktonic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Other active ingredients in cinnamon are tannins (polyphenolic compounds commonly found in most herbs) that have antibacterial properties. Villanueva et al [29] reported that tannic acid could inhibit the growth of bacteria in fish intestines by binding iron and forming a chelate that is toxic to the membranes of microorganisms. When tannins form a chelating complex with iron in the medium, this action ceases the availability of iron for microorganisms to grow under aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other active ingredients in cinnamon are tannins (polyphenolic compounds commonly found in most herbs) that have antibacterial properties. Villanueva et al [29] reported that tannic acid could inhibit the growth of bacteria in fish intestines by binding iron and forming a chelate that is toxic to the membranes of microorganisms. When tannins form a chelating complex with iron in the medium, this action ceases the availability of iron for microorganisms to grow under aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamaldehyde has been reported to inhibit Siamese fighting fish pathogens, including Vibrio cholerae, Vibrio parahaemolyticus [23], Aeromonas hydrophila [4,8,9,24,25], Pseudomonas sp. [4,9,23,29], Edwardsiella sp. [9,23], Plesiomonas shigelloides [9], Enterobacter sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Isyraqi et al (2020), the mechanism of saponin as an antibacterial is by reducing the surface tension of bacterial cell walls which causes cell permeability to increase, so that intracellular compounds will come out. Tannins have antibacterial action by causing damage to the permeability of bacterial cell walls, microsomes and lysosomes as a result of the interaction of flavonoids with bacterial DNA so that they can dissolve extracellular protein complexes (Villanueva et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Condensed tannins are composed of polymers of flavan‐3‐ols. Tannins have potential pharmacological properties, such as antibacterial, antiinflammatory, and antitumor effects (Villanueva et al, 2022; Wang et al, 2023). Tannic acid is a typical representative of hydrolyzable tannins, which significantly inhibited the expression of T3SS effector proteins in Salmonella enterica serovar Typhimurium ( S. Typhimurium ) by down‐regulating the transcription levels of two key regulatory and structural genes, sipA and sipB .…”
Section: Preclinical Studies Of Plant‐derived Antivirulence Agents As...mentioning
confidence: 99%